ARE WE CURRENTLY UNDERESTIMATING THE RISK OF SCRUM-RELATED NECK INJURIES IN RUGBY UNION FRONT-ROW PLAYERS?. Issue 7 (11th March 2014) - Brown, J; Lambert, M; Hendricks, S; Readhead, C; Verhagen, E; Burger, N; Viljoen, W
Abstract : Background: In comparison to other aspects of play in rugby union, the scrum is a relatively controlled event, which is governed by numerous safety laws. Also, the scrum, in comparison to other events occurs relatively infrequently and yet is still associated with a number of severe injuries to one positional grouping – the front-row forwards (two props and a hooker). Objective: Previous reports may have underestimated the true risk of a scrum-related neck injury to the front-row players due to an assumption that more players are exposed to this injury risk than epidemiological studies indicate. Design: A theoretical methods paper based on previously published data. Setting: Nationwide, all ages and levels of competition. Participants: Front-row rugby players with scrum-related neck injuries. Assessment of risk factors: We compared the estimated rate of injury with the same number of injury events, but with varying numbers of players in the exposure: (1) all 15 players, (2) the eight forwards and (3) the three front-row forwards. The latter category account for the majority of all scrum-related neck injuries. Main outcome measurements: N/A. Results: The incidence rate and thus risk, can be 5 fold greater when calculated for the front-row (3 players) only and not the entire team (15 players) or the forwards, as has been performed previously. By including the other five forwards (8 players in total) or other 12 players in the team (15 players in total) in the exposure calculation, the true risk of scrum-related neck injury could be underestimated as the front-row players account for the majority of all scrum-related neck injuries. Conclusions: Previously, we may have underestimated the true risk of injury scrum-related neck injuries to the front-row players. Future studies should consider reporting the scrum-related injury risk in the front-row player population only.